Penerapan Sistem Public E-Services: Portal Informasi, Layanan Administrasi dan Pengaduan pada Kantor Desa Kerta Buana - Taghfirul Azhima Yoga Siswa; Istimaroh Istimaroh; Wawan Joko Pranoto (Pusat Riset dan Inovasi Nasional, 2025)
Kerta Buana Village Office in Kutai Kartanegara Regency faces several challenges in disseminating information and administrative services and public complaint systems. Currently, administrative services and complaint processes are still carried out conventionally, where the public must come directly and wait for officers to execute the service. In addition, the limited number of experts in supporting IT devices causes the service process to remain traditional. Therefore, Kerta Buana Village Office requires a system that can provide information and administrative services digitally to the public. The proposed system is Public E-Service which includes an information portal, online administrative services, and website-based public complaints. The implementation of the Public E-Services system is expected to optimize employee performance, improve service quality, and increase public satisfaction with public services in the village government. The main objective of implementing this system is so that Kerta Buana Village can provide better public services and make it easier for the public. The implementation method uses the System Development Life Cycle (SDLC) approach which consists of five stages: planning, analysis, design, implementation, and maintenance. The planning stage focuses on priority problems and planned solutions, while the analysis stage is carried out in the first two months to collect information related to the problem. The system design was carried out for three months, and the implementation, which took five months, included the creation of the Public E-Services website as well as training and socialization for users. The maintenance phase included monitoring and evaluation with student support to ensure optimal system sustainability.